Factors that influence students in selecting student housing: a case study in Utar Sungai Long campus - Pang, Wiyett (2022)
Since 2015, the Higher Education Blueprint has made Malaysia a tertiary educational country with many educational institutions and students. Despite the growing number of students, the development for on-campus accommodation cannot fulfil the excess need for student accommodation. Thus, students travel abroad need to rent a private student housing surrounding the higher educational institution. During the selection of student housing, there are several factors students need to consider. Therefore, this research investigates the factors that influence students in selecting student housing. It is conducted in UTAR Sungai Long Campus, a private university that has no land for on-campus student housing development.